A Review on Cancer Therapy in Different Types Of Pediatric Cancers - Saini, Priyanka; Sharma, Anu; Chhimwal, Jyoti; Sharma, Samiksha; Khan, Mohd. Shahid. (Asian Journal of Pharmaceutical Research and Development, 2015)
Cancer refers to diseases in which abnormal cells divide uncontrollably and can invade various tissues nearby. This involves cluster of diseases involving alterations in the status and expression of multiple genes that confer a survival advantage and undiminished proliferative potential to somatic or germinal cells. Cancer cells display a broad spectrum of genetic alterations leading to disturbances in molecular pathways regulating cell growth, survival, and metastasis. When such changes manifest in majority of patients with a specific type of tumour, these can be used as biomarkers for detection and developing targeted therapies, besides predicting responses to various treatments. In terms of behavior, tumours are either ‘benign’ or ‘malignant’. Leukemia is most common type of cancer among the pediatric population. Cancer chemotherapy is based on tumor cell growth and how drugs affect this growth. All chemotherapy orders are written by pediatric oncologists and countersigned, usually by another physician. With recurrent disease, various salvage protocols may be used; with refractory disease, a limited number of phase I/II studies are available through the Children's Oncology Group (COG).